2014
DOI: 10.1007/s00705-014-2118-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and antigenic evolution of H9N2 avian influenza viruses circulating in Egypt between 2011 and 2013

Abstract: Avian influenza virus subtype H9N2 has been circulating in the Middle East since the 1990s. For uncertain reasons, H9N2 was not detected in Egyptian farms until the end of 2010. Circulation of H9N2 viruses in Egyptian poultry in the presence of the enzootic highly pathogenic H5N1 subtype adds a huge risk factor to the Egyptian poultry industry. In this study, 22 H9N2 viruses collected from 2011 to 2013 in Egypt were isolated and sequenced. The genomic signatures and protein sequences of these isolates were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 59 publications
12
73
0
Order By: Relevance
“…16,36,66 Although predictable, the reassortment between H5N1 and H9N2 has not been yet reported. 70 The highest incidence of H9N2 infections was in January 2012 (6.6%, 49/ 736) and concentrated mainly in the Nile Delta. 16 The routes of the introduction of H9N2 into Egypt are not yet clear.…”
Section: H9n2mentioning
confidence: 98%
See 3 more Smart Citations
“…16,36,66 Although predictable, the reassortment between H5N1 and H9N2 has not been yet reported. 70 The highest incidence of H9N2 infections was in January 2012 (6.6%, 49/ 736) and concentrated mainly in the Nile Delta. 16 The routes of the introduction of H9N2 into Egypt are not yet clear.…”
Section: H9n2mentioning
confidence: 98%
“…16 In 2011-2013, one study identified H9N2 in 24 out 60 broiler, one out of 5 layer and one out of 5 breeder flocks 69 and the second study isolated the virus from 22 broiler flocks. 70 While the majority of infected chickens showed respiratory distress 66,68 and there was a decrease in egg production in breeder and layer flocks, 68 infected quails and some broiler flocks were clinically healthy. 16,67,70 Importantly, co-infection or prior infection with H5N1 and H9N2 was also reported in many cases in poultry in Egypt.…”
Section: H9n2mentioning
confidence: 99%
See 2 more Smart Citations
“…Weakly pathogenic avian influenza H9N2 viruses have been isolated from chickens, turkeys and quails in Egypt (11)(12)(13). All the H9N2 isolates obtained between 2010 and 2013 were closely related to Middle Eastern H9N2 viruses (12,13).…”
Section: Introductionmentioning
confidence: 99%